Using lean manufacturing tools to reduce waste and loss in the production process - A case study on a production plant for bottling water - - Jabr, Hanan Saleh (Journal of Economic, Administrative and Legal Sciences, 2021)
The research aims to identify the problems that hinder the production process and the most important of these problems is the waste and waste of the available resources, whether in the raw materials used in production or the waste of the time it takes to complete the production process. And the obstacles and benefits achieved from them, using the descriptive analytical method to study the basic hypothesis that says that the use of lean manufacturing tools leads to reducing waste and loss in the production process. The research has concluded that the application of the lean system leads to reducing waste and loss in the production process and thus create value for the customer The use of lean manufacturing tools creates products that meet market needs and according to the level of demand. Among the most important recommendations is the necessity for productive institutions to take into account product quality and not focus on reducing costs in order to meet the customer's desire.
Keywords: lean manufacturing; target costing; wastage